Toward a Comprehensive Phylogenetic Reconstruction of the Evolutionary History of Mitogen-Activated Protein Kinases in the Plant Kingdom - Janitza, Philipp; Ullrich, Kristian K.; Quint, Marcel (Frontiers in Plant Science, 2012)
The mitogen-activated protein kinase (MAPK) pathway is a three-tier signaling cascade that transmits cellular information from the plasma membrane to the cytoplasm where it triggers downstream responses. The MAPKs represent the last step in this cascade and are activated when both tyrosine and threonine residues in a conserved TxY motif are phosphorylated by MAPK kinases, which in turn are themselves activated by phosphorylation by MAPK kinase kinases. To understand the molecular evolution of MAPKs in the plant kingdom, we systematically conducted a Hidden-Markov-Model based screen to identify MAPKs in 13 completely sequenced plant genomes. In this analysis, we included green algae, bryophytes, lycophytes, and several mono- and dicotyledonous species covering >800 million years of evolution. The phylogenetic relationships of the 204 identified MAPKs based on Bayesian inference facilitated the retraction of the sequence of emergence of the four major clades that are characterized by the presence of a TDY or TEY-A/TEY-B/TEY-C type kinase activation loop. We present evidence that after the split of TDY- and TEY-type MAPKs, initially the TEY-C clade emerged. This was followed by the TEY-B clade in early land plants until the TEY-A clade finally emerged in flowering plants. In addition to these well characterized clades, we identified another highly conserved clade of 45 MAPK-likes, members of which were previously described as MHKs. In agreement with their essential functions, molecular population genetic analysis of MAPK genes in Arabidopsis thaliana accessions reveal that purifying selection drove the evolution of the MAPK family, implying strong functional constraints on MAPK genes. Closely related MAPKs most likely subfunctionalized, a process in which differential transcriptional regulation of duplicates may be involved.